2011
DOI: 10.1007/s00402-011-1369-3
|View full text |Cite
|
Sign up to set email alerts
|

Osteolysis after rotator cuff repair with bioabsorbable anchors

Abstract: Although, we found a high rate of osteolysis after rotator cuff repair with bioabsorbable anchors, these results did not change the clinical outcomes after rotator cuff repair. Recurrent tears were not significantly different in both groups and are comparable to rerupture rates in prior studies. More studies are needed to verify the effect of osteolysis over the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 24 publications
4
35
1
Order By: Relevance
“…Osteolysis was diagnosed when the normal marrow fat around the suture anchors was replaced by tissue whose signal was hypointense to water on T2-weighted images (T2WI). 6 The postoperative cuff condition was classified as described by Sugaya et al . 3 We also made a note of any abnormal signals in the proximal humerus in the preoperative MRI so as not to falsely label the findings in postoperative MRI.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Osteolysis was diagnosed when the normal marrow fat around the suture anchors was replaced by tissue whose signal was hypointense to water on T2-weighted images (T2WI). 6 The postoperative cuff condition was classified as described by Sugaya et al . 3 We also made a note of any abnormal signals in the proximal humerus in the preoperative MRI so as not to falsely label the findings in postoperative MRI.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…However there are also some reports that osteolysis occurred at the site of insertion of the anchor after rotator cuff repair. 7,8) Glueck et al 7) reported a case of rotator cuff repair with development of extensive osteolysis in the humeral head. At postoperative 8 and 16 months, there were findings suggestive of significant osteolysis at the site of insertion of the anchor.…”
Section: )mentioning
confidence: 99%
“…6) The authors suggested that subtle differences in the manufacturing processes of PLDLA, oxidative degradation during or after manufacturing, and different isomer compositions between manufacturers may contribute to the different chemical properties of the final products and could have resulted in the differences in reoperation rate, loss of fixation or osteolysis. Pilge et al 8) reported a high rate of osteolysis after rotator cuff repair with PLDLA suture anchors. Of a total of 70 PLDLA anchors, 22 showed osteolytic changes on MRI scans without affecting the clinical outcomes after rotator cuff repair.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…7 These suture anchors have elicited some concern regarding the response that the glenoid bone appears to show postsurgery. Several studies 1,4,8,11,12 have found that various types of suture anchors can lead to osteolysis and cyst formation after labral reconstruction, and it is believed that these lytic changes can contribute to glenoid rim fracture, anchor pullout, or subsequent articular cartilage damage. 1,6 This study aimed to compare the glenoid bone response and osteolytic changes in 2 different types of commercially available suture anchors: traditional push-fit biocomposite suture anchor (Osteoraptor; Smith & Nephew), and a 1.9-mm all-suture anchor (Suturefix Ultra; Smith & Nephew).…”
mentioning
confidence: 99%